Different equations for determining height among the elderly: the Bambuí cohort study of aging - Vanessa de Oliveira Siqueira; Bruna Vieira de Lima Costa; Aline Cristine Souza Lopes; Luana Caroline dos Santos; Maria Fernanda Lima‐Costa; Waleska Teixeira Caiaffa (2012)
The aim of this study was to compare measured height with estimates of height derived from equations using half arm-span measurements and assess how this affects the calculation of the body mass index (BMI) among elderly individuals. Direct height measurements of a subsample of elderly individuals from the baseline sample of the Bambuí Project were compared with estimates of height derived from equations proposed by Bassey and the WHO. The data was analyzed using the McNemar test, Lin concordance correlation coefficient (CCC) and Bland-Altman method (p < 0.05). Estimates of height using the WHO method showed a low CCC in relation to measured height. For BMI, the concordance was greater. However, with this method height was found to be underestimated so leading to the overestimation of BMI. The Bassey equation showed high concordance with measured height in elderly people over 80 years of age. With respect to BMI, the WHO method resulted in a much greater prevalence of overweight, whereas the estimates derived from the Bassey method did not differ from the results obtained from direct height measurement. Height estimates using the Bassey equation were similar to the results obtained from direct measurements, suggesting that this method is applicable.